THE ROLE OF THE TEACHER AS A FACILITATOR IN THE LEARNING PROCESS: A REVIEW OF EDUCATIONAL PSYCHOLOGY - Didik Cahyono; Rusiadi (Adisam Publisher, 2026)
This research examines the role of the teacher as a facilitator in the learning process from the perspective of educational psychology. This role reflects a shift from traditional teaching methods towards a more interactive and student-centred approach, in line with constructivism theory which emphasises the importance of active learning and students' personal experiences. In addition, the social and collaborative aspects of learning are recognised through the creation of a learning environment that supports interaction and cooperation between students, in line with social constructivism theory. Finally, the teacher as facilitator also plays an important role in providing emotional support and constructive feedback, which contributes to students' emotional well-being and the improvement of the learning process. Thus, teachers‘ adoption of the facilitator role can enhance learning effectiveness and develop students’ skills and attitudes that are essential for their future success.